2006
DOI: 10.1177/0305735606067168
|View full text |Cite
|
Sign up to set email alerts
|

Songs and emotions: are lyrics and melodies equal partners?

Abstract: We explored the role of lyrics and melodies in conveying emotions in songs. Participants rated the intensity of four types of emotions in instrumental music or the same music paired with lyrics. Melodies and lyrics conveyed the same intended emotion in Experiments 1 and 3 but were mismatched in Experiments 2 and 4. The major findings in Experiments 1 and 2 were that lyrics detracted from the emotion in happy and calm music (positive emotions), but enhanced the emotion in sad and angry music (negative emotions)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
129
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(143 citation statements)
references
References 48 publications
8
129
1
1
Order By: Relevance
“…It is also worth noting that the content of lyrics may have contributed to the induced emotional states, as 91.5% of the self-selected sad music contained lyrics. This possibility is rendered probable by the findings of previous studies (e.g., Ali & Peynircioylu, 2006;Brattico et al, 2011) that suggest lyrics may be important for musicinduced sadness. However, there may be other mechanisms as well-such as emotional contagion-that contribute to sadness induced by personally relevant, familiar music, since Fantasy-the tendency to imaginatively transpose oneself into the feelings and actions of fictitious characters (Davis, 1980) -was related to higher mean sadness ratings also in Condition 3.…”
Section: Discussionmentioning
confidence: 91%
“…It is also worth noting that the content of lyrics may have contributed to the induced emotional states, as 91.5% of the self-selected sad music contained lyrics. This possibility is rendered probable by the findings of previous studies (e.g., Ali & Peynircioylu, 2006;Brattico et al, 2011) that suggest lyrics may be important for musicinduced sadness. However, there may be other mechanisms as well-such as emotional contagion-that contribute to sadness induced by personally relevant, familiar music, since Fantasy-the tendency to imaginatively transpose oneself into the feelings and actions of fictitious characters (Davis, 1980) -was related to higher mean sadness ratings also in Condition 3.…”
Section: Discussionmentioning
confidence: 91%
“…One possible reason for the considerably low success rate of both the pop music sets (P1 and P2) could be the effect of lyrics. Even though Ali and Peynircio glu (2006) demonstrated that musical features have usually more emotional significance than lyrics, nearly all the excerpts in these two Fig. 2.…”
Section: Prediction Of Valence Across Genresmentioning
confidence: 89%
“…As a result, the lyrics themselves, independently of music, may have led pupils to more clearly perceive Cape Verdeans as having similar values to their own, which may have positively affected their attitudes. What if the lyrics had expressed messages that were at odds with pupils' values (Ali & Peynircioğlu, 2006)?…”
Section: Future Studiesmentioning
confidence: 99%